Design and implementation of a multi-degrees-of-freedom cable-driven parallel robot with gripper. (29th September 2018) - Lin, Jonqlan; Wu, Chi Ying; Chang, Julian
Cable-driven parallel robots comprise driven actuators that allow controlled cables to act in parallel on an end-effector. Such a robotic system has a potentially large reachable workspace, large load capacity, high payload-to-weight ratio, high reconfigurability, and low inertia, relative to rigid link serial and parallel robots. In this work, a multi-degrees-of-freedom cable-suspended robot that can carry out pick-and-place tasks in large workspaces with heavy loads is designed. The proposed cable-driven parallel robot is composed of a rigid frame and an end-effector that is suspended from eight cables—four upper cables and four lower cables. The lengths of the cables are computed from the given positions of the suspended end-effector using a kinematic model. However, most multi-cable-driven robots suffer from interference among the cables, requiring a complex control methodology to find a target goal. Owing to this issue with cable-driven parallel robots, the whole control structure decomposes positioning control missions and allocates them into upper level and lower level. The upper level control is responsible for tracking the suspended end-effector to the target region. The lower level control makes fine positional modifications. Experimental results reveal that the hybrid control mode notably improves positioning performance. The wide variety of issues that are considered in this work apply to aerostats, towing cranes, locomotion interfaces, and large-scale manufacturing that require cable-driven parallel robots.